2016
DOI: 10.1097/nne.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

RN-BSN Students’ Perceptions of the Differences in Practice of the ADN- and BSN-Prepared RN

Abstract: This study explored RN-BSN students' perceptions of practice differences between nurses prepared with an ADN and BSN. Five themes were identified in 20 students' discussion posts: "a nurse is a nurse" at the bedside, beyond the bedside, BSN wanted, digging deeper, and appraisal. Results illustrate the need for educators to assist nurses in translating the differentiated educational competencies to the practice role of the bedside RN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…Findings from this study confirm findings by Matthias and Kim-Godwin (2016), who reported ADN-to-BSN students as not anticipating that their BSN education would change their nursing practice because their ADN education already taught them to provide safe care at the bedside. In addition, this study supports earlier findings about ADN graduates' completion of their BSN degree for career advancement and perhaps graduate education (Anbari, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Findings from this study confirm findings by Matthias and Kim-Godwin (2016), who reported ADN-to-BSN students as not anticipating that their BSN education would change their nursing practice because their ADN education already taught them to provide safe care at the bedside. In addition, this study supports earlier findings about ADN graduates' completion of their BSN degree for career advancement and perhaps graduate education (Anbari, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The findings validate and extend those of previous studies without delineating students in fully online programs from hybrid and faceto-face programs. Students' reasons for returning to school for RN-BSN program are similar to previous cited reasons such as pressure from employers and employer hiring practices resulting from the popularity of Magnet recognition programs job security and advancement [6,11,39]. Increased professional values and growth, earning respect from peers, and improving professional identity were reported as reasons for returning to school by only a few participants.…”
Section: Discussionsupporting
confidence: 64%
“…The evidence consulted confirms that students improve in therapeutic communication during the development of clinical practice, and we have not found studies that provide information on a student's evolution in the professional development dimension and care management (26,34) .…”
Section: Discussionmentioning
confidence: 80%